Components and Principles of Developing Students' Social Competence - Rasulova Hulkar Sadatovna (Scientific Trends, 2025)
This article reveals that social competence is a complex dynamic integrated system of a person's individual qualities, which ensures his ability to act in a social environment, taking into account generally accepted social norms and rules, values, as well as social positions. The student must have social knowledge and skills, experience in making decisions in various situations, and be ready to communicate effectively with the community and the environment surrounding him.
Keywords: Personality, methodology, social competence, professional activity, values, individual qualities.